PENGARUH BUDAYA ORGANISASI DAN PERILAKU KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN - Sundari Soekotjo (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2015)
The study aims to find out the effect of organizational culture, leadership behavior on the job satisfaction of the employee organization of PT Pembangunan Perumahan (Persero). A survey was conducted with a randomly selected sample of 98 employees. With all the variables put into a correlation matrix, the data was then analyzed with the path technique. The result showed that: (1) organizational culture had effect on the employee’s job satisfaction; (2) leadership behavior had effect on the employee’s job satisfaction; the results suggest that organizational culture, leadership behavior are important determinants of the job satisfaction.